2020
DOI: 10.3389/fnmol.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipids and Their G-Coupled Protein Signaling in Alzheimer’s Disease: From Physiological Performance to Pathological Impairment

Abstract: Lysophospholipids (LPLs) are bioactive signaling lipids that are generated from phospholipase-mediated hydrolyzation of membrane phospholipids (PLs) and sphingolipids (SLs). Lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P) are two of the best-characterized LPLs which mediate a variety of cellular physiological responses via specific G-protein coupled receptor (GPCR) mediated signaling pathways. Considerable evidence now demonstrates the crucial role of LPA and S1P in neurodegenerative diseases, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 194 publications
(304 reference statements)
2
16
1
Order By: Relevance
“…This indicates that S1PR1/2/3 plays an important role in the occurrence and development of RA. Furthermore, S1PR1/2/3 can couple with Gα to induce multiple signals, 31‐33 an effect that was further confirmed in our study. Pharmacological inhibition of S1PR1/2/3 downregulated the expression of Gαi, whereas the inhibition of S1PR1/3 increased the expression of Gαs.…”
Section: Discussionsupporting
confidence: 85%
“…This indicates that S1PR1/2/3 plays an important role in the occurrence and development of RA. Furthermore, S1PR1/2/3 can couple with Gα to induce multiple signals, 31‐33 an effect that was further confirmed in our study. Pharmacological inhibition of S1PR1/2/3 downregulated the expression of Gαi, whereas the inhibition of S1PR1/3 increased the expression of Gαs.…”
Section: Discussionsupporting
confidence: 85%
“…Lysophosphatidic acid is a bioactive lysophospholipid that induces cellular responses via specific GPCRs (LPA1–6). LPA is produced from lysophosphatidylcholine by the action of autotaxin ( Hao et al, 2020 ). Several studies have indicated that LPA treatment of BMECs induces BBB impairment.…”
Section: Inflammatory Mediators Involved In Bbb Dysfunction and Related Intracellular Signaling Pathways In Bmecsmentioning
confidence: 99%
“…S1P is synthesized by phosphorylation of sphingosine derived from sphingolipids by sphingosine kinases 1 and 2 (Sphk1 and Sphk2). Intracellular S1P is secreted into the extracellular space via S1P transporters (e.g., Abca1 and Spns2) where it acts as an extracellular signaling molecule through GPCRs (S1PR1–5) coupled with G q , G i , G 12/13 , and Rho proteins ( Hao et al, 2020 ; Pluimer et al, 2020 ). S1P regulates a number of biological processes including vascular development and function.…”
Section: Inflammatory Mediators Involved In Bbb Dysfunction and Related Intracellular Signaling Pathways In Bmecsmentioning
confidence: 99%
“…Cognitive disorders, such as dementia with AD, raise this bar even further since disorders such as AD are multifactorial in origin. Multiple mechanisms may lead to cognitive impairment and involve cellular injury from β-amyloid (Aβ), tau, excitotoxicity, metabotropic receptors, lipid dysfunction, mitochondrial damage, acetylcholine loss, astrocytic cell injury, oxidative stress, heavy metal disease, and cellular metabolic dysfunction with diabetes mellitus (DM) [3,4,8,14,27,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Present strategies to treat cognitive loss with AD involve therapy with cholinesterase inhibitors that may decrease some symptoms but do not alter disease progression [11,15,52,55].…”
Section: Novel Therapeutic Considerations For Cognitive Lossmentioning
confidence: 99%